Un terrain miné, un travail de déminage ou comment parler de l’oppression des femmes minorisées en tant que chercheuse de la majorité - Iavarone-Turcotte, Anne (2023)
Dans cet article, je présente la manière dont j’ai abordé, pour tenter de les atténuer, les risques découlant de ma prise de parole sur mon objet d’étude doctorale : l’oppression des femmes dans les minorités religieuses. Ces risques découlant de mon positionnement de féministe blanche occidentale, membre de la majorité libérale et laïque, et détentrice de nombreux privilèges associés à ces statuts, j’ai résolu de modifier symboliquement ce positionnement dans ma recherche. Pour ce faire, j’ai élaboré et appliqué une méthodologie réflexive dont l’un des aspects clés, présenté dans l’article, a été de (re)tourner mon regard critique vers moi.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique du nord; amériques; approches et analyses; cours; discipline; inégalités; justice sociale; phi4336; philosophie; point de vue situé; premier cycle; privilèges; pédagogie; périodes historiques; québec; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Manifestly Haraway - Haraway, Donna Jeanne (University of Minnesota Press, 2016)
"Electrifying, provocative, and controversial when first published thirty years ago, Donna Haraway's "Cyborg Manifesto" is even more relevant today, when the divisions that she so eloquently challenges–of human and machine but also of gender, class, race, ethnicity, sexuality, and location–are increasingly complex. The subsequent "Companion Species Manifesto," which further questions the human-nonhuman disjunction, is no less urgently needed in our time of environmental crisis and profound polarization. Manifestly Haraway brings together these momentous manifestos to expose the continuity and ramifying force of Haraway's thought, whose significance emerges with engaging immediacy in a sustained conversation between the author and her long-term friend and colleague Cary Wolfe. Reading cyborgs and companion species through and with each other, Haraway and Wolfe join in a wide-ranging exchange on the history and meaning of the manifestos in the context of biopolitics, feminism, Marxism, human-nonhuman relationships, making kin, literary tropes, material semiotics, the negative way of knowing, secular Catholicism, and more. The conversation ends by revealing the early stages of Haraway's "Chthulucene Manifesto," in tension with the teleologies of the doleful Anthropocene and the exterminationist Capitalocene. Deeply dedicated to a diverse and robust earthly flourishing, Manifestly Haraway promises to reignite needed discussion in and out of the academy about biologies, technologies, histories, and still possible futures."– Provided by publisher.
Keywords: LGBTQIA2+; animaux de compagnie; approches et analyses; chien; corps; cours; cyberféminisme; cyborg; discipline; discours dominant; identités LGBTQIA2+; lit4700; philosophie; point de vue situé; premier cycle; relations humains/animaux; ressource en ligne; sciences humaines; systèmes d'oppressions; technologie; thématiques

Rôle des valeurs en science: contributions de la philosophie féministe des sciences - Ruphy, Stéphanie (Écologie & politique, 2015)
Cinq décennies d’études féministes sur les sciences ont renouvelé et enrichi significativement les réflexions épistémologiques sur des notions fondamentales comme celles d’objectivité ou de preuve empirique, et plus largement sur la question du rôle des valeurs en science. Nous présentons quelques-unes des positions féministes actuelles les plus influentes au sein de la philosophie des sciences contemporaine, positions qui offrent des alternatives à l’idéal de neutralité de la science et ouvrent la possibilité d’une pratique proprement féministe des sciences. Nous discuterons également du tournant politique de la philosophie des sciences, invitée à se saisir de la question du rôle et des objectifs assignables à la science dans nos démocraties contemporaines.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; cours; discipline; discours dominant; europe; france; phi4336; philosophie; point de vue situé; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Les savoirs situés de Sandra Harding et Donna Haraway: science et épistémologies féministes - Puig de La Bellacasa, María (l'Harmattan, 2014)
« La pensée de deux auteurs incontournables des études féministes anglo-américaines : Sandra Harding et Donna Haraway est ici explorée. L'ouvrage introduit les trajets de ces deux auteures autour du statut « épistémologique » donné à l'expérience des femmes, la critique de l'objectivité dans les sciences et technosciences contemporaines, leur approche des mondes « non humains », et leurs propositions pour des savoirs « positionnés » et « situés ». »–Résumé de l'éditeur.
Keywords: approches et analyses; cours; discipline; har4600; histoire et politique; philosophie; point de vue situé; pol4212; premier cycle; savoir situé; science; sciences humaines; thématiques

Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
https://spectrum.library.concordia.ca/id/eprint/977861/1/Madden_PhD_F2013.pdf
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Feminist epistemologies - Alcoff, Linda Martín.; Potter, Elizabeth (Routledge, 1993)
Il s'agit de la première collection de théoriciennes féministes influentes à se concentrer sur le cœur de l'épistémologie traditionnelle, traitant de questions telles que la nature des connaissances et l'objectivité dans une perspective de genre.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; point de vue situé; ressource en ligne; sciences humaines; thématiques; épistémologie

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Section: 1 v. (xi-276 p.) ; 23 cm
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; épistémologie

The feminist standpoint: Developing the ground for a specifically feminist historical materialism - Hartstock, Nancy (Discovering reality: Feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science, 1983)
Keywords: approches et analyses; cours; discipline; fem1000; féminisme matérialiste; philosophie; point de vue situé; premier cycle; sciences humaines; épistémologie